139k views
4 votes
Find the center and radius of the circle whose equation is x^ (2) + y ^(2) - 6x - 2y + 4 = 0

User Pando
by
5.7k points

1 Answer

3 votes

Answer:

Explanation:

The center of a circle can be found using the equation
(x-h)^2 + (y-k)^2 = r^2 and is (h,k) from it. Notice h and k are the opposite value as in the equation.

First write the equation in this form.


x^2 - 6x + ( ?)+ y^2 - 2y + (?) + 4 = 0

Complete the square with each variable to find what numbers should go in place of the question marks.


(-6/2)^2 = -3^2 = 9


(-2/2)^2 = -1^2 = 1

Add 1 and 9 to both sides of the equation.


x^2 - 6x + 9 + y^2 - 2y + 1 + 4 = 1 + 9\\(x-3)^2 + (y-1)^2 + 4 = 10\\(x-3)^2 + (y-1)^2 = 6

So the center is (3,1) and the radius is √6.

User Paul Pepper
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.